Multifocal adenomatous oncocytic hyperplasia of the parotid gland: A report of two cases with review of the literature (Indian Journal of Case Reports, 2020)
Multifocal adenomatous oncocytic hyperplasia (MAOH) is a rare non-neoplastic condition of the parotid gland. It is also referred to as “Oncocytosis.” It accounts for approximately 0.1% of all the salivary gland lesions. The existence of this entity needs more understanding compared to its counterpart oncocytoma due to limited identification and studies. Here, we report a case series of two cases of MAOH in a 63-year-old man and in a 54-year-old woman over the left and right parotid region, respectively, both clinically operated for malignant parotid tumors. Fine-needle aspiration of both the lesions was reported with differentials of oncocytic rich lesions oncocytoma, Warthin’s tumor, and an oncocytic variant of mucoepidermoid carcinoma. Histology was proven as MAOH as it showed multiple unencapsulated nodules composed of oncocytes. Cytology alone is not sufficient for its diagnosis as they overlap with other oncocytic rich lesions. Awareness of this entity is essential for surgeons and practicing pathologists as it is a benign condition, thereby avoiding extended surgeries.